1997
DOI: 10.1080/00380768.1997.10414780
|View full text |Cite
|
Sign up to set email alerts
|

Field study of the effects of excess copper on wheat photosynthesis and productivity

Abstract: Copper concentration in wheat plants growing in a Cu-contaminated area, was 3.5-times higher than that of the control, while the total chlorophyll (a + b) content of plants growing in an ore site was significantly reduced. The significant decline of the chlorophyll concentration in the Cu-stressed wheat plants in relation to the decrease in the chlorophyll alb ratio was an indication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 34 publications
0
23
0
4
Order By: Relevance
“…On the other hand, it has also been reported that soil metal stress did not influence WUE although reducing growth. For example in the study of Maustakas et al (1997), aluminium toxicity reduced transpiration and net CO 2 assimilation to a similar extent in Thiopyrum bessarabicum. Becerril et al (1989) found that different metals may have different effects on transpiration and growth in the same plant: At similar leaf metal concentrations, Pb caused a drastic reduction of water use efficiency, while Cd inhibited transpiration and carbon assimilation to a similar degree and thus did not change WUE.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…On the other hand, it has also been reported that soil metal stress did not influence WUE although reducing growth. For example in the study of Maustakas et al (1997), aluminium toxicity reduced transpiration and net CO 2 assimilation to a similar extent in Thiopyrum bessarabicum. Becerril et al (1989) found that different metals may have different effects on transpiration and growth in the same plant: At similar leaf metal concentrations, Pb caused a drastic reduction of water use efficiency, while Cd inhibited transpiration and carbon assimilation to a similar degree and thus did not change WUE.…”
Section: Discussionmentioning
confidence: 88%
“…Water use efficiency decreased in the metal treatments as expected and in agreement with findings of other studies. Maustakas et al (1997) found that wheat plants grown on Cu-rich soil exhibited considerable less water use efficiency than plants grown on fertile soil. A copper-induced decrease of water use efficiency was also observed in solution-cultured pea plants (Angelov et al 1993).…”
Section: Discussionmentioning
confidence: 98%
“…Synthetic was generated via a wide cross of the diploid Aegilops tauschii (DD genome) with the tetraploid wheat Altar 84 (AABB genome). The population contains 114 RILs, which were mapped with 332 RFLP markers, on average 15.8 marker for each chromosome (Nelson et al 1995a,b,c, Marino et al 1996.…”
Section: Methodsmentioning
confidence: 99%
“…The toxic effect of the excess copper is often studied (recently, e.g., Ilias 2005, Agrawal andSarma 2006), however, there is a little information about the genetic background of the copper tolerance in the economically important plants. The cereals are sensitive to the high soil copper concentration: the phytotoxic effect could result in reduced fertility and in yield loss of field-cultivated wheat (Moustakas et al 1997). Selection of more resistant genotypes could provide gene sources for breeding Cu-tolerant wheat, and tolerant cultivars, which can accumulate high concentration of Cu in their shoots, could be directly used for the extraction of the metals from the polluted soils.…”
Section: Introductionmentioning
confidence: 99%
“…However, before visible changes take place in the plants, at lower concentrations of the element, they respond to environmental stress by synthesizing ethylene (Abeles et al 1992;Hyudo 1991;Rodriguez et al 1999). Cell processes take place, including a change in enzyme activities (Van Assche and Clijsters 1990; Chen et al 2000;Cuypers et al 2002), changes in the photosynthesis (Ciscato et al 1996;Moustakas et al 1997) and of chloroplast pigments (Mocquot et al 1996).…”
Section: Introductionmentioning
confidence: 97%